Brain Renin–Angiotensin System in Hypertension, Cardiac Hypertrophy, and Heart Failure - Campos, Luciana; Bader, Michael; Baltatu, Ovidiu C. (Frontiers in Physiology, 2012)
Brain renin–angiotensin system (RAS) is significantly involved in the roles of the endocrine RAS in cardiovascular regulation. Our studies indicate that the brain RAS participates in the development of cardiac hypertrophy and fibrosis through sympathetic activation. Inhibition of sympathetic hyperactivity after myocardial infarction through suppression of the brain RAS appears beneficial. Furthermore, the brain RAS modulates the cardiovascular and fluid–electrolyte homeostasis not only by interacting with the autonomic nervous system but also by modulating hypothalamic–pituitary axis and vasopressin release. The brain RAS is also involved in the modulation of circadian rhythms of arterial pressure, contributing to non-dipping hypertension. We conclude that the brain RAS in pathophysiological states interacts synergistically with the chronically overactive RAS through a positive biofeedback in order to maintain a state of alert in diseased conditions, such as cardiac hypertrophy and failure. Therefore, targeting brain RAS with drugs such as renin or angiotensin converting enzyme inhibitors or receptor blockers having increased brain penetrability could be of advantage.